(untitled) (ResearchJet Journal of Analysis and Inventions, 2022)
This article provides information on the methods of organizing and conducting laboratory training as a methodical recommendation for the practical application of the theoretical knowledge obtained for the formation of knowledge, skills and skills of students in the field of methodology of sociological research .